PENGARUH MODEL PEMBELAJARAN PROBLEM SOLVING BERBANTUAN MEDIA REALIA TERHADAP HASIL BELAJAR SISWA - Ayu Prihandari, Ni Luh; Sukardi; Masyhuri; Novi Suryanti , Ni Made; Siti Hurriyah , Daeng (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to determine the effect of problem solving model assisted by realia media on student learning outcomes in sociology subjects. This study used a quantitative approach of quasi experiment type with posttest only design with non-equivalent control group desaign. The population of this study were all students of class XI IS at SMA Negeri 4 Mataram which were distributed in 3 classes, namely class XI IS 1, XI IS 2, and XI IS 3. The sample of this study was class XI IS 1 as the experimental class and XI IS 3 as the control class which was determined by random simple random sampling technique after going through the class matching process. Data collection using multiple choice tests that have met the instrument criteria. This research data was analyzed using parametric test analysis techniques. The results showed that there was an effect of the problem solving model assisted by realia media on student learning outcomes as evidenced by the average value of the experimental class (85.56) higher than the average value of the control class (79.09). The implications of this model and media enrich and prove the theory of constructivism because both emphasize active learning, real experience, and the role of students as builders of their own knowledge.